The experience of flow in adolescence : Its relatioship with personality traits and age - Leibovich de Figueroa, Nora (2013)
The aim of this study is to assess the experience of flow and its relationship with the personality traits and the age of the adolescents. For this purpose, 224 participants of both sexes were selected, aged 12-20 years, who were examined with various tools: Flow State in adolescents (Leibovich de Figueroa & Schmidt, 2013). This is a self-report technique of 28 items that assesses the Flow State, covering all the aspects theoretically listed as components in the optimal experience of enjoyment. And a self-report Being a teenager nowadays, which evaluates 33 pairs of opposite personality characteristics that represent the personality domains of the NEO-PI-R (Costa & McCrae, 1992. Costa & McCrae, 2005, Leibovich & Schmidt, 2005). Among the found results, it was observed that in the adolescents with high scores on the scale of Flow State, the main personality trait was extroversion. Also, the influence of age on optimal flow experience appears in the chosen activities.